The Influence Of Internal And External Factors On The Level Of Non-Performing Financing In Sharia Banks In Indonesia For The Period 2014-2023 - Imam, Fathur; Purbayati, Radia (Indonesian Journal of Economics and Management, 2025)
This study aims to determine the level of non-performing financing at Islamic banks in Indonesia caused by the Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Inflation, and Unemployment Rate. This research uses an explanatory quantitative method. The population in this study were 14 Islamic Commercial Banks with a sample of 10 Islamic Commercial Banks selected using purposive sampling technique. The results of this study found that partially FDR, Inflation, and Unemployment Rate have no effect on the level of non-performing financing. Meanwhile, CAR affects the level of non-performing financing. Meanwhile, simultaneously FDR, CAR, Inflation and Unemployment Rate affect the level of non-performing financing at Islamic Banks in Indonesia for the period 2014-2023. This research provides encouragement to Islamic banks in Indonesia to continue to maintain consistency in managing capital and financing risks arising from internal and external factors